2019
DOI: 10.1536/ihj.17-656
|View full text |Cite
|
Sign up to set email alerts
|

Valve Hemodynamics and Clinical Outcomes After Transcatheter Aortic Valve Replacement for a Small Aortic Annulus

Abstract: The hemodynamics and outcomes in patients with a small aortic annulus (SAA) after transcatheter aortic valve replacement (TAVR) with a second-generation transcatheter heart valve remain unclear. We investigated whether TAVR with a Sapien XT (Edwards Lifesciences, Irvine, California) influences postprocedural valve hemodynamics and long-term outcome in high-risk SAA patients compared with surgical aortic valve replacement (SAVR). We retrospectively identified 94 SAA patients who underwent aortic valve replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Transcatheter aortic valve replacement (TAVR) is reportedly advantageous over surgical aortic valve replacement for patients with a small native aortic annulus, owing to fewer incidences of prosthesispatient mismatch (PPM) and the larger effective orifice area (EOA) achieved, associated with the absence of a sewing ring. [1][2][3][4] Valve-invalve (VIV) TAVR has drawn attention as a minimally invasive treatment for patients with degenerative bioprosthesis, 5 for whom use of TAVR will likely increase. In Japan, two different third-generation transcatheter heart valves (THVs) (self-expanding THV, Evolut R, Medtronic, Minneapolis, MN and balloon-expandable THV, Sapien 3, Edwards Lifesciences, Irvine, CA) are used for TAVR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter aortic valve replacement (TAVR) is reportedly advantageous over surgical aortic valve replacement for patients with a small native aortic annulus, owing to fewer incidences of prosthesispatient mismatch (PPM) and the larger effective orifice area (EOA) achieved, associated with the absence of a sewing ring. [1][2][3][4] Valve-invalve (VIV) TAVR has drawn attention as a minimally invasive treatment for patients with degenerative bioprosthesis, 5 for whom use of TAVR will likely increase. In Japan, two different third-generation transcatheter heart valves (THVs) (self-expanding THV, Evolut R, Medtronic, Minneapolis, MN and balloon-expandable THV, Sapien 3, Edwards Lifesciences, Irvine, CA) are used for TAVR.…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter aortic valve replacement (TAVR) is reportedly advantageous over surgical aortic valve replacement for patients with a small native aortic annulus, owing to fewer incidences of prosthesis‐patient mismatch (PPM) and the larger effective orifice area (EOA) achieved, associated with the absence of a sewing ring 1‐4 . Valve‐in‐valve (VIV) TAVR has drawn attention as a minimally invasive treatment for patients with degenerative bioprosthesis, 5 for whom use of TAVR will likely increase.…”
Section: Introductionmentioning
confidence: 99%
“…There are recent studies that have specifically compared TAVR to SAVR among patients with SAA. On short‐term follow‐up, patients who underwent TAVR had a larger EOA, lower mean gradient, and lower rate of severe PPM in comparison to SAVR patients 58,59 . Among patients with SAA, there was no difference between TAVR and SAVR with respect to EOA and rates of PPM, but the mean gradient was lower following TAVR 60 .…”
Section: Resultsmentioning
confidence: 91%
“…On short-term follow-up, patients who underwent TAVR had a larger EOA, lower mean gradient, and lower rate of severe PPM in comparison to SAVR patients. 58,59 Among patients with SAA, there was no difference between TAVR and SAVR with respect to EOA and rates of PPM, but the mean gradient was lower following TAVR. 60 This association was not present among patients with a larger aortic annulus.…”
Section: Transcatheter Avr (Tavr)mentioning
confidence: 97%
“…17,18) It has been reported that severe AS patients receiving TAVI in Japan are much older than those in Europe and the United States. 19,20) The population of patients in this trial had an average age approximately more than five years older than the populations in recent TAVI trials. 6,9,11) Moreover, in contrast to other studies evaluating sex in AS, our male and female groups were similar in terms of REVERSE REMODELING AFTER TAVI age, comorbidity, cardiac risk score, and aortic valve gradients.…”
Section: Discussionmentioning
confidence: 99%